For the Reaction Fe^+3 + 3e^- = Fe, E° is -0.036V and E° for Fe^+3 +e^- = Fe^+2 is 0.771V.
Calculate E° for Fe^+2 +2e^- = Fe.
In solution according to Book,
Let Fe^+2 +2e^- = Fe -----------(1)
Firstly, find ∆G for each equation with given E° and then combine equation (and ∆G also) . After combining equation, we get required equation and ∆G for the required equation and then use simply for ∆G = -nFE
And we get required E°.
Here my problem is -
1. How do I get equation (1) after combining those equation (Like mathematics)
How does ot work.
2. How we get ∆G for equation (1) after combining those equation's ∆G.
**Is there any alternate ways for solving this question**